Android Based Fuel and Resource Saving System - Deshmukh, Ketki; Mali, Mansi; Patil, Surendra; Jadhav, Kiran (International Journal of Computer Sciences and Engineering, 2015)
Many carpool and ride-sharing solutions have been proposed and even developed in the previous decades, but they were rarely able to attain a global user base, at least not up until recently. That was mostly because many of them were not initially designed as scalable, leaving their users without user friendly user experiences as their user base grew, and often their cell-phone or desktop client reach was not unique enough, making them available only to a small portion of mobile client devices and/or desktop users. This paper explains and describes the design concepts, distribution and cloud computing strategies the authors feel any future global carpool and ride-sharing solution could follow, making it very scalable and unique enough to successfully fulfill user requirements with user friendly user interface